The Russians are coming, again : the first Cold War as tragedy, the second as farce - Kuzmarov, Jeremy, 1979-; Marciano, J. D. (Monthly Review Press, 2018)
"A consideration of the turbulent relationship between the United States and Russia during the Trump era in light of the previous Cold War of the 1950s. The book argues that the Democrats' strategy, backed by the corporate media, of demonizing Russia and Putin in order to challenge Trump is not only dangerous, but also unjustified, misguided, and a major distraction. Includes accounts of the First Cold War's victims and dissidents."--